Establishment of two serological methods for detecting IgG and neutralizing antibodies against Crimean-Congo hemorrhagic fever virus glycoprotein - Wang, Qi; Wang, Shen; Shi, Zhikang; Li, Zhengrong; Zhao, Yongkun; Feng, Na; Wang, Tiecheng; Yan, Feihu; Xia, Xianzhu (Frontiers in Cellular and Infection Microbiology, 2024)
The Crimean-Congo hemorrhagic fever virus (CCHFV), the most geographically widespread tickborne virus, is endemic in Africa, Eastern Europe and Asia, with infection resulting in mortality in up to 30% of cases. Currently, there are no approved vaccines or effective therapies available for CCHF. The CCHFV should only be manipulated in the BSL-4 laboratory, which has severely hampered basic seroprevalence studies on CCHFV. In the present study, two antibody detection methods in the forms of an enzyme-linked immunosorbent assay (ELISA) and a surrogate virus neutralization test (sPVNT) were developed using a recombinant glycoprotein (rGP) and a vesicular stomatitis virus (VSV)-based virus bearing the CCHFV recombinant glycoprotein (rVSV/CCHFV), respectively, in a biosafety level 2 (BSL-2) laboratory. The rGP-based ELISA and rVSV/CCHFV-based sVNT were established by using the anti-CCHFV pre-GC mAb clone 11E7, known as a broadly cross-reactive, potently neutralizing antibody, and their applications as diagnostic antigens were validated for the specific detection of CCHFV IgG and neutralizing antibodies in experimental animals. In two tests, mAb clone 11E7 (diluted at 1:163840 or 512) still displayed positive binding and neutralization, and the presence of antibodies (IgG and neutralizing) against the rGP and rVSV/CCHFV was also determined in the sera from the experimental animals. Both mAb clone 11E7 and animal sera showed a high reactivity to both antigens, indicating that bacterially expressed rGP and rVSV/CCHFV have good immunoreactivity. Apart from establishing two serological testing methods, their results also demonstrated an imperfect correlation between IgG and neutralizing antibodies. Within this limited number of samples, the rGP and rVSV/CCHFV could be safe and convenient tools with significant potential for research on specific antibodies and serological samples.